2000
DOI: 10.1073/pnas.97.7.3428
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno-associated virus type 2, 4, and 5 vectors: Transduction of variant cell types and regions in the mammalian central nervous system

Abstract: Recombinant adeno-associated virus vectors based on serotype 2 (rAAV2) can direct transgene expression in the central nervous system (CNS), but it is not known how other rAAV serotypes perform as CNS gene transfer vectors. Serotypes 4 and 5 are distinct from rAAV2 and from each other in their capsid regions, suggesting that they may direct binding and entry into different cell types. In this study, we examined the tropisms and transduction efficiencies of ␤-galactosidase-encoding vectors made from rAAV4 and rA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
348
4
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(373 citation statements)
references
References 35 publications
15
348
4
2
Order By: Relevance
“…This is consistent with the findings of Lubansu et al where AAV serotype 5 was shown to be ineffective in transducing rat embryonic (E15) ganglionic eminence cultures. These data are in contrast to studies showing that AAV serotype 5 was efficient at transducing cells in adult mouse 31,32 and non-human primate brain. 33,34 This discrepancy suggests that the availability of AAV5-binding sites, such as 2,3-linked sialic acid, 35 and potential receptors may vary from gestation through to adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the findings of Lubansu et al where AAV serotype 5 was shown to be ineffective in transducing rat embryonic (E15) ganglionic eminence cultures. These data are in contrast to studies showing that AAV serotype 5 was efficient at transducing cells in adult mouse 31,32 and non-human primate brain. 33,34 This discrepancy suggests that the availability of AAV5-binding sites, such as 2,3-linked sialic acid, 35 and potential receptors may vary from gestation through to adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…27 Cross-packaging of the AAV2 vector genome into other AAV serotypes demonstrated that the amino acids of the capsids are responsible for some of the differences in cellular tropism. 16,17,26,28,29 The different capsids likely result in differences in binding to cellular receptors as evidenced by the ability of AAV1, AAV2, and AAV3 to bind to heparan sulfate, while AAV4 and 5 do not. 25,27 The receptors for AAV2 and AAV5, heparan sulfate proteoglycans and 2,3-linked sialic acid, respectively, have been determined.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Comparison of the ability of three different AAV serotypes, AAV2, 4, and 5, to transduce the mouse brain revealed that while intrastriatal injection of either AAV2 or AAV5 led to transgene-positive parenchymal cells, AAV5 resulted in the greatest number of transgenepositive cells. 17 We compared the ability of three rAAV serotypes, AAV1, 2, and 5, to achieve gene transfer in the normal cat brain. b-glucuronidase (GUSB) was used as a marker gene due to the ability to monitor enzyme expression using histochemical staining and mRNA expression using in situ hybridization on frozen brain sections.…”
Section: Introductionmentioning
confidence: 99%
“…AAV2 has shown higher transduction efficiency in glioblastoma in vitro and in vivo when compared to serotypes 4 and 5 [183]. However, other studies have demonstrated a higher distribution and transduction in the CNS when using rAAV serotypes 1 and 5 [175, 184, 185]. The different AAV serotypes have been exploited on their ability to efficiently transduce distinct regions of the brain due to different cellular tropisms [174, 183, 186].…”
Section: Aav Based Vectorsmentioning
confidence: 99%